Study of Stresses Induced in Axisymmetric Buried Thin Orthotropic Fluid Filled Clindrical Shell due to P-Wave Loading. (2018) - Dwivedi, J.P.; Krishna Lal, Radha; Singh, V.P.; Kumar, P
Abstract: Axisymmetric dynamic response and the stresses induced in a fluid –filled buried pipe due to an incident p-wave for different orthotropic parameters and different fluid is the subject of this investigation. In this work the shell is assumed perfectly bonded to the surrounding medium of infinite extent. The pipeline has been modelled as an infinitely long circular cylindrical shell buried in homogeneous, isotropic and elastic medium of infinite extent. For perfect bonding between soil and pipe, the stiffness and damping properties of soil are neglected. Results have been obtained for hard (rocky), medium hard and very soft (sandy) soil conditions surrounding the shell. The radial displacement at the shell and fluid interface (i.e., at the inner surface of the shell) is taken to be continuous while considering a fluid filled shell. The stress variations of pipe due to change in cylinder orthotropic parameters has been carefully studied. Different angles of wave incidence and different soil around shell conditions along with the different kind of fluids have been considered. The different kind of soils from soft (sandy) to hard and rocky condition has been taken into account. It is realised that the effect of fluid have a significant influence on the stresses (axial and hoop) depending on the soil conditions and the angle of incidence